2013
DOI: 10.1007/s00402-013-1869-4
|View full text |Cite
|
Sign up to set email alerts
|

Subtrochanteric shortening osteotomy combined with cemented total hip arthroplasty for Crowe group IV hips

Abstract: BackgroundTotal hip arthroplasty (THA) is a challenging surgical procedure that can be used to treat severely dislocated hips. There are few reports regarding cemented THAs involving subtrochanteric shortening osteotomy (SSO), even though cemented THAs provide great advantages because the femur is generally hypoplastic with a narrow, deformed canal.PurposesWe evaluated the utility of cemented THA with SSO for Crowe group IV hips, and assessed the relationship between leg lengthening and nerve injury. Our goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…All femoral osteotomies were stabilized with a plate and cable system in all hips, but did not use any strut allografts as mechanical support to ostoetomy site. The mean time to union has been reported between 8.8 weeks to 7.7 months for transverse subtrochanteric shortening ostetomy in the literature [7,13,21,[24][25][26][27][28]. In our study group, it was 5.2 months similarly to the previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All femoral osteotomies were stabilized with a plate and cable system in all hips, but did not use any strut allografts as mechanical support to ostoetomy site. The mean time to union has been reported between 8.8 weeks to 7.7 months for transverse subtrochanteric shortening ostetomy in the literature [7,13,21,[24][25][26][27][28]. In our study group, it was 5.2 months similarly to the previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…Imarisio et al reported the average leg lengthening was 36 mm in cementless total hip replacement for Crowe Type-IV dysplasia [24]. In a series of transverse subtrochanteric shortening osteotomies combined with cemented total hip arthroplasty the mean leg lengthening was 40.5 mm [25]. Kilicoglu et al reported that the mean greater trochanter height relative to the estimated hip center improved from 6.8 cm to −1 cm radiologically [15].…”
Section: Discussionmentioning
confidence: 96%
“…However, the risk of non-union remains a major concern during the procedure [16,17]. A limited bone contact area is a major disadvantage of transverse osteotomy, which may interfere with the bone healing process [18,19]. The consistency of the interfaces and canal diameters between the proximal and distal segments may contribute to union; the two osteotomy interfaces should be as smooth as possible to maintain their intactness [20].…”
Section: Introductionmentioning
confidence: 99%
“…Wenn die Fixation allein über ein Schaftimplantat erfolgen soll, muss in der zementfreien Anwendung ein entsprechend geeignetes Stieldesign mit Rotationsstabiltät und diaphysärer Verankerung gewählt werden. Die zementierte Schaftwahl ist ebenfalls beschrieben [34,55], birgt aber das Risiko eines Zementaustrittes in den Osteotomiespalt mit unterbleibender knöcherner Ausheilung. Sehr instruktive Beschreibungen des operativen Vorgehens sind publiziert [44,68], wobei die Abfolge einzelner Schritte bei den jeweiligen Autoren naturgemäß unterschiedlich ist.…”
Section: Femorale Verkürzungsosteotomieunclassified
“…Selbst komplexe Rekonstruktionen weisen bei der Versorgung in Zentren mit entsprechender Erfahrung gute Ergebnisse auf [34,39,44,55,59]. Im australischen Endoprothesenregister [8] werden im ersten postoperativen Jahr etwas höhere kumulative Revisionsraten bei der endoprothetischen Versorgung von Dysplasiecoxarthrosen (2,2 %; 95 %-Konfidenzintervall 1, 8) im Vergleich zu primä-ren Coxarthrosen (1,5 %; 1,4-1,5) beobachtet.…”
Section: Standzeitenunclassified